βγ-CAT, a non-lens betagamma-crystallin and trefoil factor complex, induces calcium-dependent platelet apoptosis - Gao, Qian; Xiang, Yang; Chen, Zhongming; Zeng, Lin; Ma, Xutong; Zhang, Yun (Thrombosis and Haemostasis, 2011)
In recent years, it has been reported that apoptosis may occur in platelets and play a role in the clearance of effete platelets. βγ-CAT, a newly identified non-lens βγ-crystallin and trefoil factor complex from frog Bombina maxima skin secretions, caused several in vivo toxic effects on mammals. Through determined haematological parameters of rabbits, it has been found that βγ-CAT significantly reduced the number of platelets in a time-dependent manner. Here, in order to explore the effect of βγ-CAT on platelets, washed platelets were incubated with various concentrations of βγ-CAT for 30 minutes. We found that βγ-CAT induced several apoptosis events in human platelets, including caspase-3 activation, phosphatidylserine (PS) exposure, depolarisation of mitochondrial inner transmembrane potential (ΔΨm), cytochrome c re-lease and strong expression of pro-apoptotic Bax and Bak proteins. However, βγ-CAT did not significantly induce platelet activation as detected by P-selectin surface expression, GPIIb/IIIa activation and platelet aggregation. In addition, we observed that βγ-CAT-induced PS exposure and ΔΨm depolarisation in platelets are Ca2+-dependent. Taken together, βγ-CAT can induce Ca2+-dependent platelet apoptosis but does not cause platelet activation.
Keywords: Platelet apoptosis; non-lens βγ-crystallins; trefoil factor; βγ-CAT; Ca2+